Tradiciones renovadas (AV, 1999)
Ampliación del Ayuntamiento de Murcia, arq.Moneo; Ayuntamiento Vilaseca, arq. J.Llinas; Instituto Hispano-Luso, Zamora, arq.M.d.l.Casas; Centro Cívico Monte Hermoso, R.Ercilla